A Rare Case of Partial Peripheral Thyroid Hormone Resistance Due to a Point Mutation in the Membrane Integrin Α(V)Β(3) and Concomitant Hashimoto`s Thyroiditis - Savovska, Martina; Stojanoski, Sinisa; Manevska, Nevena (ID Design 2012/DOOEL Skopje, 2019)
Peripheral resistance to thyroid hormones is a type of unresponsiveness of the peripheral cells or tissues to FT3 and/or FT4. Generalised resistance to thyroid hormones affects the pituitary gland and most of the peripheral tissues. Selective pituitary resistance or central resistance to thyroid hormones include unresponsiveness of the pituitary gland, but the peripheral tissues are responsive. Selective peripheral resistance involves peripheral tissue or cellular resistance to thyroid hormones, but the pituitary gland is responsive.